Implementasi Supervisi Akademik Pada Sekolah Dasar Negeri 44 Kota Tenate - Eksan, Wachyudi (Peneliti.net, 2024)
Every educational institution in carrying out the learning process certainly cannot be separated from problems. Principals, teachers, educators, students, and other educational stakeholders are almost certain to have problems or issues related to learning. The problems in this study are (1) how is the implementation of academic supervision in elementary schools? (2) What are the obstacles in the implementation of academic supervision in schools? While the purpose of this study is to determine the implementation of academic supervision in schools, with the following research focus: (1) implementation of academic supervision in schools, and (2). This study was conducted with a qualitative approach. Data sources in the study were determined using purposive sampling and snowball sampling techniques. Data and information in the study were obtained using three data collection techniques, namely: (1) observation, interviews and documentation. The results of the data and information were analyzed using interactive patterns, including: (1) data condensation, (2) data presentation, and (3) drawing conclusions. The results of the study indicate that the implementation of academic supervision in schools has been running well, as evidenced by the principal's work program in realizing the quality of optimal implementation of learning activities, namely by conducting academic supervision, especially on the preparation and learning tools of teachers. However, in the implementation process, the principal found obstacles, especially in providing guidance to new teachers so that the academic supervision process provided was not only limited to guidance but had entered the clinical supervision stage.